The Netherlands adjustment policy with a development cooperation dimension - Michael D. Alford (Intereconomics, 1979)
All developed market economies have, during the last two decades, suffered serious structural difficulties in their economies, due, in part, to increasing LDC competitiveness in the production of manufactured goods. Most developed countries have reacted by adopting measures aimed at restructuring their economies to take account of these trends. Only the Dutch, however, have included a development cooperation dimension into part of their general restructuring programme.
Keywords: 330; Development Assistance